PRAKTIK DUAL LISTING DI INDONESIA - Zonara, Marshya Aprilia Santhya (Jurnal Akuntansi AKUNESA, 2013)
There are several foreign companies that perform multiple share listing in Indonesia, but there are still some obstacles faced by the recording of stock that still need to be reviewed by the Indonesian Stock Exchange. Once the regulations regarding the record has addressed, the multiple listing of share can be immediately implemented. So if we want this practice of multiple share listing to be going well, we should adopt multiple share listing from Singapore. As you know Singapore has practiced multiple stocks with good record and continues to grow every year. Keywords: Dual Listing, Bursa Efek Indonesia, peraturan pencatatan